Use of robotized process automation for research management and evaluation - Alejandro Boza-Chua; Laberiano Andrade-Arenas; Natalia I. Vargas-Cuentas; Avid Roman-Gonzalez (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Universities, called entities with the responsibility of training new professionals and contributing to continuous knowledge for human development through research, seek to increase their scientific production and climb positions in research rankings. In this sense, research management is necessary and knowing which  information and communications technology tools help in this task is a great help. The main objective of this work is to identify the  information and communications technology tools that help to perform a good research management and implement a system based on Robotized Process Automation to generate a scientific information system for the University of Sciences and Humanities, for this research work was used the cascade methodology which provided several advantages and support for the structure and development of the system, for the process of the system was used the UiPath tool which is considered the best process automation tool. As a result of this research work, a system was obtained that drastically reduces the data collection time to evaluate the scientific production of researchers, thus allowing a better research management.